Poblamiento tardío en Torralba, Lorca - Martínez Rodríguez, Andrés; Matilla Séiquer, Gonzalo (Antigüedad y Cristianismo, 1998)
This paper analyses a settlement in Lorca during the late Roman period, which was isolated from al1 main Roman roads. What is of interest here was the existence of a strong, stable economic system which was a precursor of that which appeared in the high mediaeval period; furthermore this settlement, although still populated, has been inhabited from at least first century AD.